Linking pre- and post-adoption records for research in anonymised form in a data safe haven:: legal implications and support for a social licence - Jones, Kerina; Heys, Sharon; Thompson, Rachel; Griffiths, Lucy; Johnson, Rhodri; Lee, Alex; Ford, David; Broadhurst, Karen (International Journal of Population Data Science, 2020)
Introduction: The long-term health and wellbeing of adoptees is under-researched. One reason for this has been limited data accessibility regarding the adoption process, and another is a practice common in some UK jurisdictions of changing the NHS number (or equivalent) at adoption, as part of creating the new identity. The SAIL Databank holds data from the Wales Children and Family Court Advisory and Support Service (Cafcass Cymru), together with children’s social care data, and can link these with routine health and administrative data in anonymised form. However, because the linkage key at SAIL is based on an encryption of the NHS number, working with pre- and post-adoption records for longitudinal research remains a major challenge. We set out to explore the legal implications of, and social support for, linking these records for use in anonymised form for longitudinal research. Methods: We reviewed the main legislation and regulations governing the use of data about adoptees in England and Wales. We gauged support for a social licence in Wales by carrying out interviews with individuals who had been involved in the adoptions process, and by engaging with general public groups for their views. We drew out the main emerging themes and, in combination with the review, propose a way forward. Results: The legal review indicated that there are provisions in the Family Procedure Rules (England and Wales) and the General Data Protection Regulation that can be relied upon for the lawful processing of adoption data into anonymised form for research. The main points of concern about linking pre- and post-adoption records were privacy, data security, the need to limit the number of organisations involved in data sharing, and re-identification risk. The over-riding message was favourable with longitudinal research seen as strongly beneficial. Conclusion: This study has indicated that in Wales, there is no legal impediment, nor major objection from individuals involved in the adoptions process, as well as the general public for the use of adoption data in anonymised form, in a data safe haven. This includes the linkage of pre- and post‑adoption records to enable novel longitudinal research to take place. The provisos were that robust safeguards must be in place, and that the research should aim to benefit adoptees and to improve policy and practice. We conclude that it is reasonable to proceed with caution to develop practical ways to link pre- and post‑adoption records in a data safe haven.